Exploring intensification strategies of pasture-based dairy systems in Uruguay: high-productivity and inputs versus medium-productivity and simpler systems - Gil-Zibil, Lucía; Ortega, Gastón; Custodio, Diego; Loza, Cecilia; Briñón, María Pía; Chilibroste, Pablo (Frontiers in Animal Science, 2025)
The increased intensification of pasture-based dairy systems has led to greater use of external inputs, increasing the risk of nutrient losses to the environment. Limited information is available in Uruguay on how intensification strategies affect productivity and nutrient balances at the farm scale. This study compared productive variables and farm-gate nutrient balances of nitrogen (N), phosphorus (P), and potassium (K) \under two pasture-based dairy intensification strategies over three fiscal years (July 2021–June 2024). Two intensification strategies were evaluated in a 3-year completely randomized block design: (1) High Productivity (HP), with a stocking rate of 2.8 cows/ha, using bought-in conserved forage and concentrates; and (2) Medium Productivity (MP), with 1.7 cows/ha, self-sufficient in conserved forage and concentrates and featuring simplified management. Cows were paired by calving date, body condition score, body weight, and previous milk yield, then randomly assigned to each system. Farm-gate nutrient balances accounted for inputs from feed, fertilizers, biological N fixation, and atmospheric deposition, and outputs from milk, live weight changes, and bedding materials. Data were analyzed using linear mixed models, with treatment and year as fixed effects and blocks as random effects. No significant differences were observed in forage production between systems; however, HP relied more on harvesting by grazing (7,073 vs. 4,782 kg DM/ha for HP and MP, respectively; p<0.05), whereas MP had higher mechanical harvest (473 vs. 1,862 kg DM/ha for HP and MP, respectively; p<0.05). Milk (22,178 vs. 13,606 kg milk ha-1), and solids (1,907 vs. 1,184 kg solids ha-1) productivity were significantly higher for HP than for MP. Regarding nutrient inputs, feed was the main source of N for HP, whereas fertilizer was predominant for MP. For P and K, feed was the largest input in both systems. Nutrient surpluses for N, P, and K were 312 vs. 205, 82 vs. 50, and 128 vs. 44 kg/ha for HP and MP, respectively. Nutrient use efficiency did not differ significantly between treatments. Time in confinement was higher for HP (55% vs. 37%). Higher intensification increased productivity but also nutrient surpluses, highlighting the importance of infrastructure and effluent management. Additionally, effluent reutilisation emerged as an opportunity to improve nutrient use efficiency in intensified systems.